The Effect of Honey Suplementation to Physiological NaCl Solution on Sperm Quality of Catfish (Hemibarus nemurus) Semen During Storage - Indri Tri Mayang Sari; Hamdan Alawi; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe aim of this study to evaluate the effect of honey supplementation in physiological NaCl on sperm motility, viability, fertility and hatching rate of riverine bagrid catfish (Hemibagrus nemurus) during short storage. This experiment used Completely Random Design (CRD) with 5 treatments and 3 replications, namely P0 : 0% honey in 100% physiological NaCl, P1 : 0,2% honey in 99,8% physiological NaCl, P2 : 0,4% honey in 99,6% physiological NaCl, P3 : 0,6% honey in 99,4% physiological NaCl, P0 : 0,8% honey in 99,2% physiological NaCl. The result showed that the addition honey in physiological NaCl on sperm storage significantly affect sperm quality of catfish during 96 hours of storage. The result showed that the best quality sperm of catfish treated by P2 was higher (P<0,05) than other treatment. In addition, the optimal storage time was 36 hours which was very good motility and highest viability (67,5%). After 12 hours storage, fertilization rate 76,5% with hatching rate 78% but after 96 hours storage, fertility decrease until 19,39% with hatching rate 58,97%. Keywords : Hemibagrus nemurus, honey, spermatozoa